Spontaneous Spinal Epidural Hematoma in a Patient on Apixaban for Nonvalvular Atrial Fibrillation - Ahmad El Alayli; Logeswari Neelakandan; Hicham Krayem (Case Reports in Hematology)
Background. With the rise in the use of direct oral anticoagulants (DOACs), more hemorrhagic complications are being encountered. Since the first description of a case of spontaneous spinal epidural hematoma (SSEH) related to the utilization of DOACs in 2012, there have been few reports describing a similar association. However, no cases so far have reported an association between SSEHs and apixaban. Case Description: A 76-year-old lady, with a history of nonvalvular atrial fibrillation, presented with a new onset of progressive left lower and upper extremity weakness. She reported back pain and numbness in the left leg up to the knee along with numbness in the left arm up to the shoulder. A CT scan of the neck was suggestive of an epidural hematoma extending from C2-C3 level to C6-C7. As the patient was on apixaban at the time, surgical treatment was delayed for two days to decrease the risk of intraoperative bleeding. Nine days later, she was discharged. Her physical exam was almost unchanged from that on presentation, except for resolution of pain and minimal improvement in motor power in her left lower extremity from 1/5 to 2/5 distally. Conclusions. Spinal hematomas represent surgical emergencies with earlier intervention portending better outcome. Based on the few case reports that point to DOACs as a potential culprit, it appears that a high suspicion index resulting in earlier SSEH diagnosis and intervention is crucial for improved neurological outcome and recovery. Prompt diagnosis remains a challenge, especially that SSEH can mimic cerebrovascular accidents.